Unveiling the factors shaping corporate tax behavior: an empirical study - Ningsih, Melly Agustina; Ruwanti, Gemi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research investigates the determinants of corporate tax management practices through an empirical analysis. It examines the influence of various factors, including profitability, leverage, capital intensity ratio, presence of independent commissioners, firm size, and access to tax facilities.Design/Methodology/Approach: Multiple linear regression analysis was employed as the research methodology. The study focused on manufacturing companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange during the period from 2018 to 2021, utilizing a purposive sampling approach—the final sample comprised 18 companies that met the specified criteria.Research Findings: The results indicated that profitability and tax facilities exhibited a negative impact on tax management, while leverage had a positive influence. Conversely, the capital intensity ratio, presence of independent commissioners, and company size did not significantly affect tax management.Theoretical Contribution/Originality: Effective tax management can enhance company compliance with tax obligations and mitigate the likelihood of aggressive tax strategies.Practitioner/Policy Implications: This research provides a valuable benchmark for companies to implement sound tax management practices aligned with tax regulations. Additionally, it offers insights for policymakers to refine tax regulations accordingly.